2018
DOI: 10.1007/s00128-018-2281-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Parameters, Induction of Lipid Peroxidation, and ATPase Activity in the Liver and Kidney of Oreochromis niloticus Exposed to Lead and Mixtures of Lead and Zinc

Abstract: The purpose of this investigation was to evaluate the effects of lead (Pb) and lead + zinc (Zn) combination on the oxidative stress, total ATPase and Pb accumulation in the tissues of Oreochromis niloticus (Linnaeus, 1758). The fish were exposed to 0.1 mg/L Pb (T1), 1.0 mg/L Pb (T2) and mixtures of 0.1 mg/L Pb and 0.5 mg/L Zn (M1); 1.0 mg/L Pb and 5.0 mg/L Zn (M2) for 7 and 21 days. Pb accumulation, total ATPase activity, several antioxidant enzyme activities such as catalase, glutathione peroxidase (GPX), glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition, it is noted that O. niloticus is a widely distributed freshwater fish and is economically important in terms of consumption. For these reasons, we chose to conduct our study on this species to determine the possible deleterious effects of FLX exposure on fish health [23] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is noted that O. niloticus is a widely distributed freshwater fish and is economically important in terms of consumption. For these reasons, we chose to conduct our study on this species to determine the possible deleterious effects of FLX exposure on fish health [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, lead is non-biodegradable and accumulates in the body, which causes lead poisoning to remain one of the world's most common health problems (2)(3)(4). Lead can cause various physiological, biochemical and behavioral disorders in the central and peripheral nervous system, hematopoietic system, cardiovascular system, kidney, liver and reproductive system, and destroy the integrity of the biological mechanism of oxidative stress (1,5). As one of the main excretion pathways of lead in organisms, the kidney is the target organ of lead cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Lead (Pb) is widely distributed in nature and used in human life, but it is also a highly toxic pollutant ( 1 ). Although people are aware of its hazards and have tried to control the exposure levels of lead in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…These biomarkers might be examined in key organs such as the gills, liver, and kidney, that have vital functions, for example, respiration, excretion, accumulation, and biotransformation of xenobiotics (Hinton & Lauren, 1990; Rey et al, 2020). Nile tilapia, Oreochromis niloticus , is a fish that has a wide distribution throughout the world as a result of its economic importance (Firidin, 2018). Recent studies have shown that atrazine was able to cause biochemical and histological changes in multiple organs of this species such as in the liver, blood, gills, and spleen (Neamat‐Allah et al, 2020; Oliveira et al, 2018; Ventura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%